How Does Risk Management Improve Farmers’ Green Production Level? Organic Fertilizer as an Example - Wang, Xiaohuan; Ma, Yifei; Li, Hua; Xue, Caixia (Frontiers in Environmental Science, 2022)
Improving the risk management ability of farmers is the critical path to promote environmental sustainability under the dual background of frequent risks and strong vulnerability of farmers. The existing literature mainly analyzed the impact of risk preference and risk perception on green production behavior from the perspective of subjective cognition. However, there is lack of research on risk management ability on farmers' green production behavior. This study used the survey data of farmers from Shaanxi, Sichuan, Zhejiang and Anhui provinces in China. On the basis of ensuring the validity and authenticity of the data, this study constructed the risk management capability index system of farmers from the individual, collective and government level. The two-stage sample selection model was used to empirically analyze the impact mechanism of risk management on green production behavior. The results show that: Risk management is the key factor to affect green production behavior. Among them, membership, government subsidies and income level significantly promote green production level. Moreover, risk management can not only directly affect the green production level of farmers, but also promote farmers' green production behavior by expanding the scale of operation, improving their sense of responsibility, and enhancing behavioral responsibility. Therefore, it is necessary to improve farmers' risk management ability. Additionally, expand farmers' operation scale by promoting land transfer, strengthen farmers' sense of responsibility by strengthening technology publicity and improve their behavior responsibility, so as to promote environmental sustainability.